ALTERED LIPID PROFILE IN HYPOTHYROIDISM: A BIOCHEMICAL VIEWPOINT - Dv, Krishna Veni; Kundoor, Neetha; Bashetti, Srilatha; Rayaprolu, Prashnathi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Context: Overt hypothyroidism is the most common endocrine disorder associated with a decrease in 3,5,3’-triiodothyronine and 3,5,3’,5’-tetraiodothyronine levels and increase in thyroid-stimulating hormone (TSH) levels. Thyroid hormones (THs) regulate all major metabolic pathways. THs play an important role in the synthesis, metabolism, and transport of lipids. Thyroid failure is associated with various biochemical and molecular alterations. Hypothyroidism is the common cause of secondary dyslipidemia as well as cardiovascular risk. Objective: The present review focuses on alterations in lipid metabolism associated with hypothyroidism leading to cardiovascular risk. Methods: The data source is from PUBMED, Google Scholar, and EMBASE. The study is a part of our previous research in studying the variations in lipid profile and transaminases in overt hypothyroidism. Result: The serum total cholesterol, low-density lipoprotein cholesterol (LDL-C), apolipoprotein B (apo B), lipoprotein (a) (Lp[a]), and triglycerides are elevated in individuals with overt hypothyroidism. In addition, it was also observed that the endothelial dysfunction, normal/depressed systolic function, left ventricular diastolic dysfunction at rest, as well as systolic and diastolic dysfunction on effort was observed in hypothyroidism. Conclusion: THs play an important role in the regulation of lipid metabolism. Hypothyroidism is also linked with altered hemodynamics. The atherogenic lipid profile along with other predisposing factors may contribute to the coronary artery disease.